The SARS-CoV-2 envelope protein disrupts barrier function in an in vitro human blood-brain barrier model - Ju, Jiahang; Su, Yuwen; Zhou, You; Wei, Hui; Xu, Qi (Frontiers in Cellular Neuroscience, 2022)
Patients with coronavirus disease 2019 (COVID-19) have been frequently reported to exhibit neurological manifestations and disruption of the blood-brain barrier (BBB). Among the risk factors for BBB breakdown, the loss of endothelial cells and pericytes has caused widespread concern. Recent studies have revealed that severe acute respiratory syndrome coronavirus 2 envelope (S2E) protein caused cell death. We tested the hypothesis that the S2E protein alone could induce BBB dysfunction. The S2E protein bound to human BBB-related cells and inhibited cell viability in a dose- and time-dependent manner. Importantly, the S2E protein disrupted barrier function in an in vitro BBB model composed of HCMEC/D3 (brain endothelial cell line), HBVP (brain vascular pericyte), and U87MG (astrocyte cell line) cells and suppressed the expression of major genes involved in maintaining endothelial permeability and function. In addition, the S2E protein crossed the HCMEC/D3 monolayer. The S2E protein triggered inflammatory responses in HCMEC/D3 and U87MG cells. Taken together, these results show for the first time that the S2E protein has a negative impact on the BBB. Therapies targeting the S2E protein could protect against and treat central nervous system manifestations in COVID-19 patients.